Case Study of Nursing Care in Children of Typoid Fever with Ineffective Intervention of Termoregulation in Child Care Room Rsia Sitti Khadijah - Dewi Modjo; Andi Akifa Sudirman; Sri Yulian Hunowu; Fadli Husain (Journal of Community Health Provision, 2023)
Good fulfillment of children's basic needs will ensure that children's health is maintained and their development will not be disturbed. The most dangerous threat in reducing children's health status is infectious disease. One of them is typhoid fever. The main complaint found in children is fever. Fever in children requires separate treatment and handling that is different compared to adults. To overcome this problem, a typhoid action plan is carried out, namely monitoring the temperature at least every 2 hours, giving warm water compresses, giving parental fluids, and collaborating with doctors about administering antipyretic drugs. This research is a quantitative study using a quasi-experimental design that provides treatment or intervention to research subjects and then the effect of the treatment is measured and analyzed. The research design used is a case study design approach. This design is used to see changes after being given warm compresses to patients with impaired thermoregulation. The sample in this study were 3 respondents, the data collection technique was using observation sheets. The results of this study have shown an optimal scale because children's thermoregulation is effective.